2020
DOI: 10.1515/ijamh-2019-0179
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians’ knowledge, attitudes and practices surrounding menstruation and feminine products

Abstract: ObjectiveThis study investigates whether primary care pediatricians adhere to the American Academy of Pediatrics (AAP) recommendations by routinely evaluating patients’ menstrual cycles and educating patients about menstruation and feminine products. Additionally, this study examines pediatricians’ knowledge and attitudes surrounding menstrual health topics.MethodsA 53-item online questionnaire was developed to evaluate pediatricians’ knowledge, attitudes and clinical practices regarding menstruation-related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A recent national survey of AAP members found that 25–33% reported either not routinely providing AG, not asking about the last menstrual period (LMP), or not discussing menstruation at all. 7 Male pediatricians were less likely to provide AG, ask about menses patterns, and had overall lower knowledge of the menstrual cycle. 7 A review of electronic medical records (EMR) from New Jersey adolescents aged 12–21 found less than five percent and ten percent of family physicians and pediatricians, respectively, obtained a history inclusive of menarche, LMP, length of cycle, and presence of associated symptoms.…”
Section: Evidence Suggests Insufficient Pediatric Engagement On Menst...mentioning
confidence: 99%
“…A recent national survey of AAP members found that 25–33% reported either not routinely providing AG, not asking about the last menstrual period (LMP), or not discussing menstruation at all. 7 Male pediatricians were less likely to provide AG, ask about menses patterns, and had overall lower knowledge of the menstrual cycle. 7 A review of electronic medical records (EMR) from New Jersey adolescents aged 12–21 found less than five percent and ten percent of family physicians and pediatricians, respectively, obtained a history inclusive of menarche, LMP, length of cycle, and presence of associated symptoms.…”
Section: Evidence Suggests Insufficient Pediatric Engagement On Menst...mentioning
confidence: 99%
“…18 Prior research has noted that male pediatricians are less likely to discuss menstruation with postmenarchal patients and report feeling less knowledgeable about menstruation than their female colleagues. 18 This same survey also revealed variability in pediatricians' ability to correctly answer questions about the average length of bleeding during menstruation and their self-reported levels of understanding regarding tampons, pads, and menstrual cups. 18 Considering midwives' expert clinical knowledge and specialization in relationship-based, reproductive health care that focuses on communication, health education, diversity awareness, and community health, 6 midwives are in a unique position to recognize and address the general lack of understanding regarding menstruation in a sensitive, culturally competent, and effective way.…”
Section: Interpersonalmentioning
confidence: 99%
“…Furthermore, and quite alarmingly, knowledge limitations regarding what constitutes a normal menstrual cycle also extend to health care professionals 18 . Prior research has noted that male pediatricians are less likely to discuss menstruation with postmenarchal patients and report feeling less knowledgeable about menstruation than their female colleagues 18 .…”
Section: Social‐ecological Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, tampons can better satisfy women’s needs for physical exercise (e.g. swimming) when menstruating ( Singer et al, 2020 ). As such, tampons may benefit many Chinese women’s health, well-being, and quality of life during menstruation.…”
mentioning
confidence: 99%